Pengaruh Dosis Poc Top G2 Terhadap Pertumbuhan Vegetatif Tanaman Sorgum (Sorgum bicolor L. Moench) - Nduang, Anton Ndana; Nganji, Marten Umbu; Ndapamuri, Melycorianda Hubi (Sandalwood Journal Of Agribusiness And Agrotechnology, 2023)
Sorghum is a cereal plant that is very useful, including the seeds can produce flour as a substitute for wheat, the stems produce sap which can be used as sugar and used as animal feed. Sorghum also has considerable potential to be developed in Indonesia because sorghum plants are able to adapt to marginal land because they are tolerant of less fertile soil or critical soil, sorghum plants are relatively resistant to pests and disease. This research aims to determine the response of vegetative growth of sorghum plants to doses of TOP G2 liquid organic fertilizer. This research was conducted at the Wira Wacana Christian University Field Laboratory, Sumba in July – September 2023. This research used 5 treatments with 4 replications. The results of this research were that giving Top G2 liquid organic fertilizer (POC) had a real effect on plant height, giving Top G2 POC on the number of leaves had a real effect, giving Top G2 POC on leaf area had no real effect, giving Top G2 POC on diameter. stems did not have a real effect on stem diameter, giving POC Top G2 on flowering time did not have a real effect on flowering time. The best recommended dosage is in treatment P4=8 ml Poc Top G2+ 992 ml water/plant.